An Enhanced Generalized Plasticity Model for Coarse Granular Material considering Particle Breakage - W. J. Cen; J. R. Luo; W. D. Zhang; M. S. Rahman (Advances in Civil Engineering)
In this study, an enhanced constitutive model is developed for coarse granular soil within the framework of generalized plasticity (Pastor, Zienkiewicz, and Chan, 1990). In this model, particle breakage is also considered by introducing the state parameter and the compression index into the plastic modulus, loading vectors, and plastic flow direction vectors of a generalized plasticity model. The calibration of constitutive parameters of the enhanced model is addressed in detail. The numerical simulation of triaxial tests for two types of coarse granular soils under different confining pressures is carried out to illustrate the particle breakage performance of the enhanced model. The good agreement between numerical results and experimental data indicates that the enhanced model can accurately characterize the influence of particle breakage on essential behavior of coarse granular soils.